Analisis Layanan Jamsostek Mobile Dan Kepuasan Pengguna Di BPJS Ketenagakerjaan Karanganyar - Anatasya Putri Jaya Dewi; Chairul Huda Atma Dirgatama (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The Jamsostek Mobile (JMO) application is a digital innovation by BPJS Ketenagakerjaan designed to accelerate service access for participants anytime and anywhere. The purpose of this study is to describe the types of services provided, focusing on the core services available within the JMO application, and to assess user satisfaction levels. The method used is a descriptive quantitative approach, by distributing questionnaires to 100 active JMO users at BPJS Ketenagakerjaan Karanganyar. The data analysis employed multiple linear regression using the End User Computing Satisfaction (EUCS). The study's findings indicate that content, format, ease of use, and timeliness have a positive and significant impact on user satisfaction, whereas accuracy does not show a significant effect. These results highlight the importance of improving the quality of information in certain aspects to support user satisfaction with the JMO digital service. Keywords: BPJS Ketenagakerjaan, EUCS, Jamsostek Mobile, User Satisfaction, Digital Services